2019
DOI: 10.1002/cncr.32546
|View full text |Cite
|
Sign up to set email alerts
|

Fertility preservation before breast cancer treatment appears unlikely to affect disease‐free survival at a median follow‐up of 43 months after fertility‐preservation consultation

Abstract: BACKGROUND:The objective of this study was to determine whether fertility preservation (FP) with oocyte/embryo cryopreservation is associated with differences in disease-free survival (DFS). METHODS: This retrospective study included patients aged 18 to 45 who were diagnosed with invasive breast cancer between 2007 and 2017 and were seen for FP consultation at a university fertility center before cancer treatment. The primary endpoint, DFS, was defined as the time from FP consultation until patients developed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 27 publications
5
41
1
Order By: Relevance
“…FP after diagnosis of breast cancer is considered a safe option [24,42]. Even in women with estrogen receptor-positive breast tumors, small retrospective studies have shown no detrimental effect of FP with the estrogen-positive tumor in situ [28,[42][43][44][45]. Stimulation protocols that add letrozole or tamoxifen have been successfully implemented and keep serum estradiol close to physiologic levels during the cycle [43,46,47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FP after diagnosis of breast cancer is considered a safe option [24,42]. Even in women with estrogen receptor-positive breast tumors, small retrospective studies have shown no detrimental effect of FP with the estrogen-positive tumor in situ [28,[42][43][44][45]. Stimulation protocols that add letrozole or tamoxifen have been successfully implemented and keep serum estradiol close to physiologic levels during the cycle [43,46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Even in women with estrogen receptor-positive breast tumors, small retrospective studies have shown no detrimental effect of FP with the estrogen-positive tumor in situ [28,[42][43][44][45]. Stimulation protocols that add letrozole or tamoxifen have been successfully implemented and keep serum estradiol close to physiologic levels during the cycle [43,46,47]. Live birth after breast cancer, even in endocrine sensitive tumors, is currently considered safe [48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…Also in the subgroup of patients who underwent neoadjuvant chemotherapy, disease-free survival was similar between the two groups (HR, 1.4; 95% CI, 0.2-9.1). 52 Another cross-sectional study of breast cancer patients undergoing COS for fertility preservation before neoadjuvant chemotherapy included 40 women with hormone-receptor positive breast cancer. 53 COS with letrozole and tamoxifen was used in this protocol.…”
Section: Burning Questions During the Oncofertility Counseling Of Youmentioning
confidence: 99%
“…38 Peak estrogen levels during the few days of stimulation are onefifth to onetenth the levels main tained over a period of several months during pregnancy. 39 All studies to date have shown similar or better cancer outcomes for patients with breast cancer who underwent ovarian stimula tion compared to matched patients who did not. [39][40][41][42] However, all these studies had relatively short followup durations (< 7 yr), and, in several, there were potentially important differences between case and control participants.…”
Section: Controlled Ovarian Stimulation For Fertility Preservationmentioning
confidence: 99%
“…39 All studies to date have shown similar or better cancer outcomes for patients with breast cancer who underwent ovarian stimula tion compared to matched patients who did not. [39][40][41][42] However, all these studies had relatively short followup durations (< 7 yr), and, in several, there were potentially important differences between case and control participants. 43 In the only study that included a substantial number of women who underwent ovar ian stimulation before surgical removal of the tumour, no increase in cancer recurrence was seen after a median followup duration of 43 months.…”
Section: Controlled Ovarian Stimulation For Fertility Preservationmentioning
confidence: 99%